KONSEPTUALISASI OMNIBUS LAW DALAM MENYELESAIKAN PERMASALAHAN REGULASI PERTANAHAN - Firman Freaddy Busroh (Arena Hukum, 2017)
AbstractOne of the factorsthat hampers theimprovement of the investment climatein Indonesia is due to regulatory issues. Regulatory issues related to several industries including the land sector. Based on data from the Ministry of Agricultural and Spatial Planning / National Land Agency of Republic of Indonesia there are about 632 regulations related to land whereas 208 are no longer valid leaving only 424 regulations applicable. Regulation of some 424 hadimplementationproblems and conflicts between agencies.The primary key of law enforcement begins with the quality of theregulation. Due to regulation which has many shortcomings that need to be addressed to improve the investment climate in Indonesia. To overcpme these problems the Minister of Agrarian and Spatial Planning / National Land Agency of the Republic of Indonesia, Mr. Sofyan Jalil  threw the idea of omnibus law to resolve regulations problems that influence the growth of investment in Indonesia. Sofyan jalil said that the government is discussing the legislation remedial solutions through the Omnibus Law. Omnibus Law's existence has been known in legal theories from common law countries. However, the existence of omnibus law is still lessknownamong the academic community of the faculty of law in Indonesia. For that purpose than this article to understand the omnibus law and its use to resolve the regulatory issues in Indonesia. AbstrakSalah satu faktor yang menghambat peningkatan iklim investasi di Indonesia disebabkan karena permasalahan regulasi. Permasalahan regulasi terkait dengan beberapa bidang industri diantaranya adalah bidang pertanahan. Berdasarkan data yang dirilis dari Kementerian Agraria dan Tata Ruang/Badan Pertanahan Nasional Republik Indonesia ada sekitar 632 regulasi yang terkait bidang pertanahan dimana 208 peraturan sudah tidak berlaku lagi sehingga yang berlaku 424 regulasi. Regulasi sebanyak 424 beberapa memiliki permasalahan penerapannya dan benturan antar instansi. Padahal kunci utama penegak hukum dimulai dari kualitas mutu regulasi yang berlaku. Akibat regulasi yang memiliki banyak kekurangan maka perlu untuk dibenahi karena menjadi faktor penghambat peningkatan iklim investasi di Indonesia. Untuk mengatasi permasalahan tersebut maka Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia Bapak Sofyan Jalil melontarkan gagasan konsep Omnibus Lawuntuk menyelesaikan pemasalahan regulasi yang menghambat pertumbuhan investasi di Indonesia. Sofyan jalil mengatakan bahwa  pemerintah tengah menggodok solusi perbaikan undang-undang melalui Omnibus Law. Keberadaan Omnibus Law sudah dikenal dalam teori-teori hukum. Teori Omnibus Law berasal dari negara yang menganut sistem hukum common law. Akan tetapi keberadaan Omnibus Lawmasih kurang diketahui dikalangan civitas akademika fakultas hukum di Indonesia. Untuk itu tujuan daripada tulisan ini untuk memahami Omnibus Lawdan penggunaannya untuk membenahi permasalahan regulasi di Indonesia.